Modelling and Simulation of the Pyrolysis Distillate Recycling Process - Komil Usmanov; Jaloliddin Eshbobaev; Noilakhon Yakubova (Proceedings)
The global chemical sector has seen substantial changes in recent years. In particular, gas processing and fractionation remain one of the most important parts of the industry. Recycling waste products from gas processing is one of today’s urgent problems. In this regard, the development of new, import-substituting chemical products based on the processing of hydrocarbon raw materials is of particular importance. Pyrolysis distillate and pyrolysis oil are secondary raw materials for the production of naphthalene and aromatics. Hydrocarbons, indene, phthalic anhydride, and other valuable chemical products are necessary for industry. Therefore, research aimed at improving the complex technology of the waste processing of gas–chemical complexes is an urgent task and requires an optimal solution. In this paper, the model of the pyrolysis process is simulated in the Aspen Plus modelling package. The developed model was also used to study the effect of temperature on the pyrolysis process and showed that there is an optimal temperature for chain fractions. To evaluate the technical efficiency of the process, the Aspen Plus simulation model was developed, and the model made it possible to accurately predict the mass shares of the hydrocarbon product. The analysis of the calculated data shows that as the pressure in the technological process is increased from 0.1 to 3.0 MPa, the vapor density of pyrolysis distillate increases up to 30 times. When the temperature rises to 350 °C, the density of distillate vapor decreases by an average of 1.51 times.